A Systematic Review and Meta-analysis Comparing Anticoagulation versus No Anticoagulation and Shorter versus Longer duration of Anticoagulation for Treatment of Isolated Distal Deep Vein Thrombosis - Lim, Ming Sheng; Ariyarajah, Anita; Oldmeadow, Christopher; Hall, Alix; Enjeti, Anoop K. (Seminars in Thrombosis and Hemostasis, 2017)
Isolated distal deep vein thrombosis (DVT) represents an important clinical problem but there is no consensus regarding its management. The aim of this review was to evaluate the safety, efficacy, and shorter versus longer duration of anticoagulation in patients with isolated distal DVT. A systematic search was conducted using MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systemic Reviews. Studies reporting rates of symptomatic pulmonary embolism (PE), recurrent DVT, proximal extension, and/or major bleeding were included. Fourteen studies (six randomized controlled trials, eight cohorts) involving 2,918 patients met the eligibility criteria (with a total of 13 meeting criteria for the meta-analysis). Compared with no anticoagulation, anticoagulation was associated with a significant reduction in proximal extension (odds ratio [OR]: 0.29; 95% confidence interval [CI]: 0.13–0.67; p < 0.004), recurrent DVT (OR: 0.16; 95% CI: 0.04–0.65; p = 0.01), and the composite end-point of proximal extension/PE (OR: 0.34; 95% CI: 0.16–0.72; p = 0.005); however, no significant differences in PE (OR: 0.47; 95% CI: 0.17–1.34; p = 0.16) or major bleeding (OR: 1.49; 95% CI: 0.33–6.86; p = 0.60) were observed. Anticoagulation for a longer duration (≥8 vs. ≤6 weeks) was associated with a significant reduction in proximal extension (OR: 0.23; 95% CI: 0.11–0.48; p < 0.001) but not for other outcomes.
Keywords: isolated; distal; calf; deep vein thrombosis; anticoagulation